Evaluation of an electroless nickel interlayer on the fatigue & corrosion strength of chromium-plated AISI 4340 steel - Nascimento, M. P.; Voorwald, HJC; Souza, R. C.; Pigatin, W. L. (Amer Electroplaters Soc Inc, 2001)
Despite the fact that chromium electrodeposition results in protection against wear and corrosion, combined with chemical resistance and good lubricity, the reduction in fatigue strength of base metal and environmental requirements causes one to search for possible alternatives. To improve the fatigue and corrosion resistance of AISI 4340 steel, an experimental study has been made for an intermediate electroless nickel layer deposited on base metal. The objective of this study was to analyze the effect of nickel underplate on the fatigue and corrosion strength of hard-chromium-plated AISI 4340 steel. Deposition of the conventional wear-resistant hard chromium plating leads to a decrease in mechanical properties of the base metal, especially the fatigue strength. Rotating bending fatigue tests results indicate better performance for conventional hard chromium plating. Good corrosion resistance in salt fog exposure was obtained for the accelerated hard chromium plating. Experimental data showed higher fatigue and corrosion resistance for samples prepared with accelerated hard chromium plate over electroless nickel plate, when compared with samples without electroless nickel underplate.